Switch from abiraterone plus prednisone to abiraterone plus dexamethasone at asymptomatic PSA progression in patients with metastatic castration‐resistant prostate cancer. (4th September 2018) - Fenioux, Charlotte; Louvet, Christophe; Charton, Emilie; Rozet, Francois; Ropert, Stanislas; Prapotnich, Dominique; Barret, Eric; Sanchez‐Salas, Rafael; Mombet, Annick; Cathala, Nathalie; Joulia, Marie‐Liesse; Molitor, Jean‐Luc; et al.
Abstract : Objective: To evaluate the effects of switching from prednisone (P) to dexamethasone (D) at asymptomatic prostate‐specific antigen (PSA) progression in patients with metastatic castration‐resistant prostate cancer (mCRPC) treated with abiraterone acetate (AA). Materials and Methods: Among 93 patients treated with AA between January 2013 and April 2016 in our institution, 48 consecutive asymptomatic patients with mCRPC, who experienced biochemical progression on treatment with AA+P 10 mg/day, were included. A corticosteroid switch to AA+D 0.5 mg/day at PSA increase was administered until radiological and/or clinical progression. The primary endpoint was progression‐free‐survival (PFS). A prognostic score based on independent prognostic factors was defined. Results: The median time to PSA progression on AA+P was 8.94 months. The median PFS on AA+D and AA+corticosteroids (P then D) was 10.35 and 20.07 months, respectively. A total of 56.25% of patients showed a decrease or stabilization in PSA levels after the switch. In univariate analysis, three markers of switch efficiency were significantly associated with a longer PFS: long hormone‐sensitivity duration (≥5 years; median PFS 16.62 vs 4.17 months, hazard ratio [HR] 0.30, 90% confidence interval [CI] 0.16–0.56); low PSA level at the time of switch (<50 ng/mL; median PFS 15.21 vs 3.86 months, HR 0.33, 90% CI 0.18–0.60); and short time to PSA progression on AA+P (<6 months; median PFS 28.02 vs 6.65 months, HR 0.41 (90% CI 0.21–0.81). In multivariate analysis, hormone sensitivity duration and PSA level were independent prognostic factors. Conclusion: A steroid switch from P to D appears to be a safe and non‐expensive way of obtaining long‐term responses to AA in selected patients with mCRPC. A longer PFS has been observed in patients with previous long hormone sensitivity duration, and/or low PSA level and/or short time to PSA progression on AA+P.